Developing electronic modules assisted by augmented reality to improve motivation and critical thinking skills - Witha Ananda Putri; Evy Yulianti (Research and Development in Education (RaDEn), 2025)
Changes and developments in education can occur due to technological developments. Technology and the internet in schools have not been fully utilized to create interactive and effective teaching materials. This research aims to produce teaching materials in the form of valid, practical, and effective augmented reality-assisted electronic modules to improve students' motivation and critical thinking skills. The research method is research and development (R&D) using the Hannafin and Peck model which has three phases (need asses, design, and develop/implement) each phase is evaluated and revised. The subjects of the study were 72 students of class XI (phase F). Data were collected from interviews, product validation questionnaires, trial questionnaires, learning motivation observation sheets, learning motivation questionnaires, and critical thinking skills essay questions. The results of the study showed that the electronic module assisted by augmented reality coordination system material was valid after the validation process from material experts 100% and media experts 97,5 with very high criteria. Augmented reality-assisted electronic module products are practically used by students from the results of the trial questionnaire with an average of 95% which means it is included in the very high criteria. Augmented reality-assisted electronic modules are also effective in increasing learning motivation in the high category because the results had an average difference of 6,75 higher than those using PowerPoint and critical thinking skills in the medium category.